Mass Cytometry Identifies Distinct Lung CD4+ T Cell Patterns in Löfgren’s Syndrome and Non-Löfgren’s Syndrome Sarcoidosis - Kaiser, Ylva; Lakshmikanth, Tadepally; Chen, Yang; Mikes, Jaromir; Eklund, Anders; Brodin, Petter; Achour, Adnane; Grunewald, Johan (Frontiers in Immunology, 2017)
Sarcoidosis is a granulomatous disorder of unknown aetiology, characterised by accumulation of activated CD4+ T cells in the lungs. Disease phenotypes Löfgren’s syndrome (LS) and “non-LS” differ in terms of clinical manifestations, genetic background, HLA association and prognosis, but the underlying inflammatory mechanisms largely remain unknown. Bronchoalveolar lavage fluid cells from four HLA-DRB1*03+ LS and four HLA-DRB1*03- non-LS patients were analysed by mass cytometry, using a panel of 33 unique markers. Differentially regulated CD4+ T cell populations were identified using the Citrus algorithm, and t-stochastic neighbourhood embedding (t-SNE) was applied for dimensionality reduction and single-cell data visualisation. We identified 19 individual CD4+ T cell clusters differing significantly in abundance between LS and non-LS patients. Seven clusters more frequent in LS patients were characterised by significantly higher expression of regulatory receptors CTLA-4, PD-1 and ICOS, along with low expression of adhesion marker CD44. In contrast, twelve clusters primarily found in non-LS displayed elevated expression of activation and effector markers HLA-DR, CD127, CD39, as well as CD44. Hierarchical clustering further indicated functional heterogeneity and diverse origins of T cell receptor Vα2.3/Vβ22-restricted cells in LS. Finally, a near-complete overlap of CD8 and Ki-67 expression suggested larger influence of CD8+ T cell activity on sarcoid inflammation than previously appreciated. In this study, we provide detailed characterisation of pulmonary T cells and immunological parameters that define separate disease pathways in LS and non-LS. With direct association to clinical parameters such as granuloma persistence, resolution or chronic inflammation, these results provide a valuable foundation for further exploration and potential clinical application.